Extended ankle and foot fasciotomy as an enhancement to the surgical treatment of patients with prolonged ischemia of the lower extremities - Mišović Sidor; Ignjatović Dragan; Jevtić Miodrag; Tomić Aleksandar (Vojnosanitetski Pregled)
Aim. To present the technique and efficacy of extended ankle and foot fasciotomy, as a surgical limb-salvage procedure associated with the successful revascularization after the gold interval. Method. A retrospective review of six patients at the age of 16−79 years (mean 39) in the period from 1996 to 2003, treated with the extended ankle and foot fasciotomy. There were four males undergoing the delayed treatment of war injuries to the lower extremity, and two females with atherosclerotic occlusive disease (a. illiacae dex and a. poplitealis dex.). The average ishemic time in the wounded patients was 22 hours (range, 14−30 hours), and ischemic time in occlusive disease (range, 48−72 hours). Clinical signs, indications, surgical access and the technique of extended ankle and foot fasciotomy was reported. Results. The obtained results were classified as early and late. There was no cases with lethal outcome. Incisional wounds closed 15 days after the intervention, using secondary suture or skin transplant sec. Thiersch. The satisfactory functional results were achieved in 4 of the patients, 1 had a small edema, while amputation was performed in 1 patient. Conclusion. In cases of prolonged foot ischemia with edema and paresthesia in the toes, extended ankle and foot fasciotomy should be performed as a surgical limb-salvage procedure.